CHEM ICAL COMPOSITIONS AND PHYTOCHEM ICAL SCREENING OF THE SEEDS OF GARC/NIA KOLA (BITTER KOLA) - Asaolu, M F (Biological Sciences - PJSIR, 2003)
Chemical compositions and pit tochemical screening of the fresh seeds of Garci11ia kola ( cl eight) have been determined The results sho cd that the samples contmned lugh moisture content 75 50% while tl1e ash content was folmd to be 5.90°,o. Carbohydrare was 10.85%. crude fat "as 14.50% and crude protein was found to be very low 4.25° o Thc resultsobtained rc\’ealed that the most abundant mineral in the scedsor’Garci11i11 kola issodium (2t 5. 0ppm) The seeds ofGarci11ia kola also contain Mg. Cd. 7.n, K and Fe, ho, cvcr. Mn. Pb. Cu. Cd and Co ere 1101 detected. Prclim1nar phytochemicul sere<,mng indicalcd the presence of phyHllc. tnnnin , oxalate. cyanate. saponins and anthraquinoncs "ith cyanate having the highest ,·aluc.